Hydrophilic Surfaces Turning of Graphene Nano Platelets by 1,3,6-Trihydroxyxanthone: π–π Stacking Interaction Affair in 2-D - Yuanita, Emmy; Sirojuttolibin, Sirojuttolibin; Dharmayani, Ni Komang Tri; Ulfa, Maria; Septiyana, Maulida; Sudirman, Sudirman (Universitas Gadjah Mada, 2025)
Graphene nanoplatelet (GNP) has a good potential to be developed as a drug carrier material. In this study, the interaction of GNP with one type of drug, namely 1,3,6-trihydroxyxanthone (THX), has been studied. The results of XRD analysis and FTIR uptake show an excellent interaction between THX and GNP through the π–π stacking channel. This interaction makes the GNP surface more polar and soluble in the aqueous media. THX-graphene shows physical and chemical stabilities, where THX can be released under specific and controlled conditions. The results of this study show the potential of utilizing graphene as a drug carrier material for more specific disease targets with a longer drug release time.